Cardio-Oncology Management of Toxicities in the Era of Immunotherapy - Russo, Antonio; Maurea, Nicola; Farmakis, Dimitrios; Giordano, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana, 2022)
The development of immunotherapy in oncology field has revolutionized the prognosis of many types of cancer. The immune checkpoint inhibitors target receptors whose inhibition increases the activity of immune system cells against tumor cells. In recent years, new immunotherapies have been studied and approved in a growing number of tumors including melanoma, non-small cell lung cancer (NSCLC), and renal cell cancer (RCC). This volume provides a complete and updated state-of-art review regarding the management of cardiovascular toxicities from new immunotherapies. The manuscript is divided into different sections starting from the relationship between cancer and immune system to let the reader understand the new molecular concepts under immunotherapy development. Subsequent chapters describe specifically the immunotherapy options in solid tumor treatment and the main features of the immuno-related cardiovascular complications. This volume is written by experts in the oncological and cardiovascular fields and aims to provide to clinicians who approach current cancer patients a useful tool to move through the paths of modern cardio-oncology. An important section would afford the most relevant interventions needed to manage the cardiac events, suggesting how to reduce their impact and effects on oncological outcomes. The text concludes by addressing future perspectives in the cardio-immunology field, discussing many aspects such as the early detection of cardiovascular damage and the potential role of liquid biopsy in new damage-related biomarkers discovery.
1. Background: Immunology and cancer -- 2. Available immunotherapy drugs in oncology -- 3. Immunotherapy adverse events -- 4. Pathophysiology of cardiac toxicity -- 5. Cardiac risk factors for immunotherapy -- 6. Diagnostic methods of cardiac immunotherapy damaging -- 7. Biomarkers of early cardiotoxicity -- 8. Management of Patients with Cardiac Toxicity: the point of view of the cardiologist -- 9. Management of patients with cardiac toxicity: the point of view of the oncologist -- 10. Future perspectives.
Keywords: Oncology; Cardiology; Pathology; Internal medicine; Oncology; Cardiology; Pathology; Internal Medicine; Cardiovascular Diseases -- etiology; Cardiotoxicity -- complications; Neoplasms -- drug therapy; Antineoplastic Agents -- toxicity; Cardiotoxicity -- therapy; Cancer Survivors